The Inventory Control System’s Weaknesses Based on the Accounting Postgraduate Students’ Perspectives - Essia Ries Ahmed; Tariq Tawfeeq Yousif Alabdullah; Lutfi Ardhani; Eskasari Putri (Universitas Negeri Malang, 2021)
The decisions made by the management in recording the amount of selling inventory in the year before the real year are as important as determining and defining the economic order size in the inventory management system. However, studies on accounting management, accounting education, and even operational management did not sufficiently discuss and evaluate such procedures to consider whether or not manipulations, frauds, or mistakes were made by the management. An obvious understanding to determine this kind of action by the managers considered as a vital element to the accounting education is represented in the recent study on the accounting postgraduate students by identifying their opinions in determining and describing whether the inventory management is weak or not and there are violations or not. The recent study is considered qualitative conducted by asking questions to 32 accounting postgraduate students regarding to the weaknesses of inventory management. The findings show that inventory management was not appropriately conducted and there were several problems and violations made by the sales managers. The other findings show that management inventory was used by the sales managers to sell the inventory in line with promoting their interests as they apply an earning management behavior. The findings also demonstrate that such case is not considered as a fraud but as a manipulation behavior.